PENGARUH GREEN PACKAGING TERHADAP GREEN BRAND LOVE DI MODERASI PERCEIVED ETHICAL QUALITY - Nala Ratih; Islamuddin Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the Effect of Green Packaging on Green Brand Love in Moderation of Perceived Ethical Quality on Wardah Consumers in Bengkulu City. This study uses a quantitative approach with a survey method, where data is obtained through distributing questionnaires to Wardah consumers in Bengkulu City. Data analysis techniques used include SEM-PLS analysis with the help of statistical programs. Based on the results of the SEM-PLS analysis, it shows that green packaging has a positive and significant effect on green brand love on Wardah consumers in Bengkulu City with a path coefficient value of 0.462, a t-statistic value of 5.214 (>1.96) and a p-value of 0.000 (<0.05). These results indicate that the better consumer perception of environmentally friendly packaging used by Wardah products, the higher the level of consumer love for the brand. The results of the study indicate that perceived ethical quality has a positive and significant effect on green brand love with a path coefficient value of 0.389, a t-statistic of 4.103 (>1.96) and a p-value of 0.000 (<0.05). This indicates that the higher the consumer perception of the ethical quality of a product, the higher the level of consumer love for the Wardah brand. Based on the results of the moderation test, it shows that perceived ethical quality is able to moderate the relationship between green packaging and green brand love with an interaction coefficient value of 0.214, a t-statistic of 2.487 (>1.96) and a p-value of 0.013 (<0.05). This indicates that perceived ethical quality strengthens the influence of green packaging on green brand love among Wardah consumers in Bengkulu City. Keywords: Green Packaging, Green Brand Love, Perceived Ethical Quality, Wardah